INSTAGRAM DAN PERUBAHAN AKTIVITAS BERWISATA MASYARAKAT BANYUMAS - Dian Bestari Santi Rahayu; Itsna Hidayatul Khusna (Fakultas Dakwah dan Komunikasi, 2021)
The purpose of this study was to see changes in the tourism activities of the Banyumas community due to the presence of Instagram. This research is a qualitative descriptive study. The object of the research is tourists who visit natural and artificial tourism places in Banyumas Regency as well as tourist objects that use Instagram as a promotional medium. Data is collected through observation, surveys, interviews and documentation through literature. From the research, the results obtained are that the first Instagram plays a role in finding information about tourist objects and as a means of self-existence, tourist activity in tourist attractions is based on status and dignity, there is a strong impulse to upload photos on Instagram, a tourist attraction that gives rise to a trend of instagramble tourism, and the utilization of Instagram as a tourism promotion media in Banyumas.Keywords: Instagram, Tourism Activity, Banyumas